2008
DOI: 10.1007/s10238-008-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the biometabolism genes CYP1A1, GSTM1, GSTT1 and GSTP1 in bladder cancer

Abstract: Numerous enzymes, including Cytochrome P450s (phase I) and Glutathione-S-transferases (phase II), are involved in the metabolic activation and detoxification of carcinogens. Epidemiological studies have consistently demonstrated that bladder cancer is strongly associated with cigarette smoking, and the risk for the development of this neoplasia may be modified by individual differences in carcinogen-metabolizing genes. We investigated the relationship between polymorphisms in the CYP1A1, GSTM1, GSTT1, and GSTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 55 publications
2
25
1
Order By: Relevance
“…The results of meta-regression analyses revealed that sources of heterogeneity were not from any of the factors mentioned above (ethnicity, BC confirmation method, genotyping method, and quality score) in all three genetic models (data not shown). Galbraith plots identified that the study by Grando et al (Grando et al, 2009) was the outlier and main contributor to heterogeneity in the three comparison models (Figure 2). Separate forest plots omitting the outlier study were conducted in each genetic model, the degree of heterogeneity decreased significantly (G vs. A: I 2 = 15.4%, P Q = 0.317; GG+AG vs. AA: I 2 = 0.0%, P Q = 0.437) with the insignificance result remaining the same (G vs. A: OR = 0.92, 95% CI = 0.71-1.18, P = 0.507; GG+AG vs. AA: OR = 0.86, 95% CI = 0.64-1.15, P = 0.305).…”
Section: Meta-analysis Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of meta-regression analyses revealed that sources of heterogeneity were not from any of the factors mentioned above (ethnicity, BC confirmation method, genotyping method, and quality score) in all three genetic models (data not shown). Galbraith plots identified that the study by Grando et al (Grando et al, 2009) was the outlier and main contributor to heterogeneity in the three comparison models (Figure 2). Separate forest plots omitting the outlier study were conducted in each genetic model, the degree of heterogeneity decreased significantly (G vs. A: I 2 = 15.4%, P Q = 0.317; GG+AG vs. AA: I 2 = 0.0%, P Q = 0.437) with the insignificance result remaining the same (G vs. A: OR = 0.92, 95% CI = 0.71-1.18, P = 0.507; GG+AG vs. AA: OR = 0.86, 95% CI = 0.64-1.15, P = 0.305).…”
Section: Meta-analysis Resultsmentioning
confidence: 97%
“…CYP1A1*2B A/G (I1e462Val) and Bladder Cancer Risk: As established above, six studies, with a total of 908 cases and 815 controls, evaluated the association of BC risk in I1e462Val A/G mutation Fontana et al, 2009;Grando et al, 2009;Ozturk et al, 2011;Berber et al, 2013;Fu et al, 2013). According to our results, no significant association between this polymorphism and BC risk was found in all genetic models in the overall populations: i) G vs. A (OR = 1.04, 95% CI = 0.74-1.47, P = 0.810); ii) GG vs. AA (OR = 1.47, 95% CI = 0.70-3.07, P = 0.308); iii) AG vs. AA (OR = 0.97, 95% CI = 0.74-1.27, P = 0.819); iv) GG+AG vs. AA (OR = 1.01, 95% CI = 0.68-1.48, P = 0.970); v) GG vs. AG+AA (OR = 1.45, 95% CI = 0.70-3.02, P = 0.317).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations